Entrepreneurial orientation and effectiveness of Small and Medium Agro-based Enterprises (SMAEs) in Malaysia - Mediating effect of knowledge and network strategies / Amran Awang ... [et al.] - Awang, Amran; Subari, Khairul Anwar; Ahmad, Zainal Ariffin; Said Asghar, Abdul Rashid (Institute of Research, Development and Commercialization (IRDC), 2007)
This paper aims to explore the mediating role of knowledge and networking on entrepreneurial orientation (EO)-performance relationships among the small and medium agro-based enterprises (SMAEs) in Malaysia. The concept is somewhat vague. Thus knowledge-based and networking strategies are some basic features to understand in the relationships. EO, knowledge and network were entrepreneurial capabilities under the purview ofthe resourcebased view (RBV) that werefound to explain firm seffectiveness. Results of the study noted that EO dimensions among SMAEs entrepreneurs showed strong relationship to knowledge-base elements of human capital development and tacit knowledge and network variables (consist of strategic alliance and social network capabilities).